Validations and descriptions of European syntaxa of vegetation dominated by lichens, bryophytes and algae - Bültmann, Helga; Roux, Claude; Egea, José Maria; Julve, Philippe; Bricaud, Oliver; Giaccone, Giuseppe; Täuscher, Lothar; Creveld, Marijke; Di Martino, Vincenzo; Golubić, Stjepko; Takeuchi, Nozomu (Lazaroa, 2015)
Fourty-two high-rank syntaxa and seven associations of the thallophyte system of syntaxa are either described as new or validated in this paper. Among those, there are the following nine classes: Aspicilietea candidae, Caulerpetea racemosae, Desmococcetea olivacei, Entophysalidetea deustae, Gloeocapsetea sanguineae, Mesotaenietea berggrenii, Naviculetea gregariae, Porpidietea zeoroidis, Roccelletea phycopsis. Eleven orders and ten alliances as well as three associations are described or validated: the Aspicilietalia verruculosae (incl. Aspicilion mashiginensis and Teloschistion contortuplicati), the Caulerpetalia racemosae (incl. Caulerpion racemosae), the Desmococcetalia olivacei (incl. Desmococcion olivacei), the Dirinetalia massiliensis, the Fucetalia vesiculosi (incl. Ascophyllion nodosi), the Gloeocapsetalia sanguineae, the Lecideetalia confluescentis (incl. Lecideion confluescentis), the Mesotaenietalia berggrenii (incl. Mesotaenion berggrenii, Mesotaenietum berggrenii and Chloromonadetum nivalis), the Naviculetalia gregariae (incl. Oscillatorion limosae and Oscillatorietum limosae), the Porpidietalia zeoroidis (incl. Porpidion zeoroidis), and the Roccelletalia fuciformis (incl. Paralecanographion grumulosae). Further, five orders, seven alliances and four associations, classified in known classes, were described as well. These include: the Bacidinetalia phacodis, the Agonimion octosporae and the Dendrographetalia decolorantis (all in the Arthonio radiatae-Lecidelletea elaeochromae), the Staurothelion solventis (in the Aspicilietea lacustris), the Pediastro duplicis-Scenedesmion quadricaudae and the Pediastro duplicis-Scenedesmetum quadricaudae (both in the Asterionelletea formosae), the Peccanion coralloidis and the Peltuletalia euplocae (both in the Collematetea cristati), the Laminarion hyperboreae, the Saccorhizo polyschidi-Laminarietum and the Alario esculenti-Himanthalietum elongatae (all in the Cystoseiretea crinitae), the Delesserietalia sanguinei, the Delesserion sanguinei and the Delesserietum sanguineae (all in the Lithophylletea soluti), as well as the the Rinodino confragosae-Rusavskietalia elegantis and the Rhizocarpo geographici-Rusavskion elegantis (both in the Rhizocarpetea geographici).